Identifcation and virulence of entomopathogenic fungi, Isaria javanica and Purpureocillium lilacinum isolated from the whitefy, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) in Malaysia - Sani, Ibrahim; Jamian, Syari; Saad, Norsazilawati; Abdullah, Sumaiyah; Mohd Hata, Erneeza; Jalinas, Johari; Ismail, Siti Izera (Egyptian Society for Biological Control of Pests (ESBCP), 2023)
Background Three of entomopathogenic fungi, identifed as Isaria javanica (Cjc-03 and Cjw-01) and Purpureocillium lilacinum (TS-01) were found naturally infecting the whitefies, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) on chili and tomato plants. All the isolates were identifed by morphological characterization and molecular identifcation (ITS region amplifcation). The virulence of the three isolates was evaluated against nymphs of B. tabaci at three diferent concentrations (1— 106 , 1— 107, and 1— 108 conidia/ml) under laboratory conditions and on adults of B. tabaci at one conidia concentration (1— 107 conidia/ml) under laboratory and glasshouse conditions. Results Isaria javanica showed the highest virulence against B. tabaci nymphs and adults in both laboratory and glasshouse conditions. I. javanica exhibited the highest mortality in the laboratory against B. tabaci, nymphs at the highest concentration (1— 108 conidia/ml) 8 days post-inoculation. Likewise, in the laboratory bioassay, B. tabaci, adults, Cjc-03 isolate exhibited maximum mortality (80.0), followed by Cjw-01 isolate (77.5), and TS-01 isolate (65.0) at the concentration of 1— 107 conidia/ml at 7 days post-inoculation. The highest mortality rate (63.45) was recorded by the Cjc-03 isolate and TS-01 (54.22) isolate at 3 days post-inoculation in glasshouse bioassay using the concentration of 1— 107 conidia/ml of each of the 2 isolates (Cjc-03 and TS-01) against B. tabaci adults. Conclusion Overall, the findings showed that both isolates of I. javanica and P. lilacinum reduced the number of eggs, nymphs, and adults emergence of B. tabaci, following the application of 1— 107 conidia/ml on tomato leaves in the glasshouse. The newly isolated strains could be developed as a potential commercial biopesticide for managing B. tabaci.